Effect of zero tillage basin planting and N nutrition on growth, yield, water productivity and nitrogen use efficiency of late planted broccoli (Brassica oleracea var italica) in North East Hilly Region of India - YADAV, G S; DATTA, M; BABU, SUBHASH; DEBNATH, CHANDAN; BHOWMIK, S N; ANSARI, M A; NGACHAN, S V (The Indian Journal of Agricultural Sciences, 2014)
Our study showed, the zero tillage basin planting with 180 kg N/ha enhanced the marketable yield, water productivity in broccoli (Brassica oleracea L. var italica) and save 71.2% water over flat bed planting with conventional tillage. Study revealed, it is an alternative system for small holder farmers of North East India for growing late planted broccoli under limited water availability.